Interstitial Lung Disease Associated With Autoimmune Rheumatic Diseases: Checklists for Clinical Practice - Bosello, Silvia Laura; Beretta, Lorenzo; Del Papa, Nicoletta; Harari, Sergio; Palmucci, Stefano; Pesci, Alberto; Rechichi, Gilda; Varone, Francesco; Sebastiani, Marco (Frontiers in Medicine, 2021)
Background: Interstitial lung diseases (ILDs) are often associated with rheumatic diseases. Their early diagnosis and management are not only difficult, but also crucial, because they are associated with major morbidity and mortality and can be the first cause of death in autoimmune rheumatic diseases (ARDs). Objectives: By using methodologies, such as Nominal Group Technique (NGT) and Delphi Survey, the aims of this study were (1) to establish consensus between pulmonologists, radiologists and rheumatologists experienced in the management of ARD-ILD; (2) to highlight the importance of a multidisciplinary approach; and (3) to provide clinicians with a practical tool aimed at improving the prompt recognition and follow-up of ILD associated with ARDs and of any possible rheumatic conditions underlying ILD. Results: During the NGT round, the Steering Committee defined 57 statements to be used in the Delphi survey. A total of 78 experts participated in the Delphi survey, namely 28 pulmonologists, 33 rheumatologists and 17 radiologists. During this round, consensus on agreement was reached in 47 statements, while disagreement was not reached in any statements. A secondary questionnaire was drafted by the Steering Committee to address statements that did not reach consensus. Delphi Panellists took part also in the second-questionnaire survey. Answers from both surveys were used to draft two checklists of “red flags” sign or symptom suggestive of ILD and ARD, respectively, and two checklists on identification and monitoring of rheumatoid arthritis and systemic sclerosis ILD. Limitations: This study is a consensus work, which cannot produce empiric data, and is limited to the Italian scenario. Conclusions: This work showed a high level of agreement, but also shows some divergent opinions between different experts. This underlines the importance of a multidisciplinary approach. Eventually, we believe the drafted checklists can help clinicians in the diagnosis and follow-up of ILD-ARD.